Workplace training in Europe - Andrea Bassanini; Alison L. Booth; Giorgio Brunello; Maria de Paola; Edwin Leuven (Institute for the Study of Labor (IZA), 2005)
This paper reviews the existing evidence on workplace training in Europe in different data sources - the CVTS, OECD data and the European Community Household Panel. We outline the differences in training incidence and relate these differences to the private costs and benefits of training, and to institutional factors such as unions, employment protection and product market competition. We ask whether there is a case for under-provision of training in Europe and examine alternative policies aiming both at raising training incidence and at reducing inequalities in the provision of skills.
Keywords: J24; 330; training; Europe; training policies